(untitled) (Research, Society and Development, 2021)
Objectives: To determine the prevalence of patient identification in emergency room units, and to verify the adherence of the multidisciplinary team of emergency room units to the patient identification data conference. Methods: Descriptive, observational, quantitative approach and cross-sectional research, carried out in emergency rooms at three public university hospitals, between July and September / 2017. The population consisted of 240 patients who remained in this unit for more than 24 hours. Results: Identification with a bracelet was found in 87.1% of the patients and a prevalence of 48.3% in the adherence of the health team to the verification of patient identification data. When comparing hospitals, adherence to the data conference was: HA = 27.1%; HB = 40.3% and; HC = 77.3%. Conclusion: In the services investigated, patient identification was not carried out systematically, especially in the step of checking the data before performing procedures.